Penentu Pola Pembiayaan Kredit Pemilikan Rumah pada Preferensi Masyarakat Perkotaan - Valentine, Bunga Prifa; Suharno, Suharno; Ahmad, Abdul Aziz (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze whether the factors of property values, religiosity, procedures, promotions influence people's preferences in choosing conventional and sharia mortgage financing in Purwokerto. The sample in this research is the people in Purwokerto, especially the people who are interested in taking mortgages with a sample size of 100 respondents. The method used in this research is random sampling technique. The analytical method used is logistic regression analysis, which is a regression model in which the dependent variable is a category, namely conventional banks and Islamic banks. The data processing uses the help of IBM SPSS. The results of this study indicate that property value has no effect on people's preferences in choosing conventional and sharia mortgage financing in Purwokerto, religiosity has a significant influence on people's preferences in choosing conventional and Islamic mortgage financing in Purwokerto, procedures have a significant influence on people's preferences in choosing financing. Conventional and sharia mortgages in Purwokerto, and procedures have a significant effect on people's preferences in choosing conventional and sharia mortgage financing in Purwokerto. Keywords: property value, religiosity, procedure, promotion.